2012
DOI: 10.1074/jbc.m111.293928
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR)-mediated Positive Feedback of Protein-tyrosine Phosphatase ϵ (PTPϵ) on ERK1/2 and AKT Protein Pathways Is Required for Survival of Human Breast Cancer Cells

Abstract: Background:To investigate the functional role of PTP⑀ in human breast cancer cell lines. Results: PTP⑀ was up-regulated in human breast cancer cells in an EGFR-and ERK1/2-dependent manner. PTP⑀ displayed a positive role in survival of human breast cancer cells. Conclusion: PTP⑀ generates a positive feedback regulatory loop required for survival of human breast cancer cells. Significance: PTP⑀ could be a putative target in breast cancer treatment.Increased tyrosine phosphorylation has been correlated with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Dominantnegative ISG20 (interferon-stimulated exonuclease gene 20 kD) inhibits angiogenic function in human umbilical vein ECs by a less well-defined mechanism (31). Other transcripts that were reduced included GADD45B, the DNA repair protein (reviewed in Reference 32); GPCR5B, best studied in differentiation of macrophages (33); and PTPRE, a phosphatase that can up-regulate EGF receptor signaling (34). Transcripts that were increased in IPAH versus control PAECs by RNAseq include high-mobility group AT-hook 1 (HMGA1) and endothelial nitric oxide synthase (NOS3).…”
Section: Discussionmentioning
confidence: 99%
“…Dominantnegative ISG20 (interferon-stimulated exonuclease gene 20 kD) inhibits angiogenic function in human umbilical vein ECs by a less well-defined mechanism (31). Other transcripts that were reduced included GADD45B, the DNA repair protein (reviewed in Reference 32); GPCR5B, best studied in differentiation of macrophages (33); and PTPRE, a phosphatase that can up-regulate EGF receptor signaling (34). Transcripts that were increased in IPAH versus control PAECs by RNAseq include high-mobility group AT-hook 1 (HMGA1) and endothelial nitric oxide synthase (NOS3).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, upregulation of IQGAP3 inhibited apoptosis of BC cells, accompanied with increased p-ERK1/2 and Bcl2 expression and decreased Bax expression, and Kaempferol counteracted the effect of IQGAP3 upregulation. ERK1/2, one of the most extensively studied groups of MAPKs, is a major determinant in diverse cellular processes, including apoptosis, proliferation, and survival [33,34], and has been observed to be associated with BC [35]. It has been reported that Kaempferol-induced apoptosis of BC cells involves sustained activation of ERK signaling [8], and IQGAP3 is reported to regulate cell proliferation by mediating Ras-dependent ERK signaling [17].…”
Section: Discussionmentioning
confidence: 99%
“…PTPRE contributes to Erk1/2 and Akt activation, improve the cell viability and colony formation of breast cancer cell lines. EGFR, Erk and PTPRE forms a positive feedback loop 52. Overexpression of PTPRE in murine mammary epithelium leads to mammary hyperplasia and higher occurance of tumor 53, suggesting that PTPRE itself is not sufficient to induce cell transformation.…”
Section: Ptpre In Cancermentioning
confidence: 99%
“…In normal cells, PTPRE inhibits the activation of insulin receptor 26, 27 and PDGFB signaling 28. Unlike that in normal cells, PTPRE positively regulates the receptor tyrosine kinase EGFR signaling 52. The underlying mechanisms as to how PTPRE regulates the signaling of different receptor tyrosine kinases in opposite ways between normal and cancer cells remain obscure, and should be further explored.…”
Section: The Similarities and Differences Of Ptpre In Normal And Cancmentioning
confidence: 99%